PENTINGNYA DIVERSIFIKASI PRODUK PADA PERUSAHAAN - Al Farisi, M. Naufal Hilmy; Anggraeni, Rila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
SUPERBLOCK is a business engaged in the paving block industry focusing on paving in Malang City. This study aims to identify internal and external conditions and formulate appropriate business strategies using the QSPM matrix analysis technique. This study uses the Internal External (IE) matrix, the Strength, Weakness, Opportunity and Threat Matrix (SWOT) and the Quantitative Strategic Planning Matrix (QSPM). The results of this study are that the internal and external environment in the SUPERBLOCK is strong enough to respond to the opportunities and threats in the SUPERBLOCK. Based on the environmental analysis, a strategy was obtained to create standard operating procedures and improve workflow to improve the quality of SUPERBLOCK operational performance.